A 1-Diopter Vertical Prism Induces a Decrease of Head Rotation: A Pilot Investigation - Matheron, Eric; Zandi, Ava; Wang, Danping; Kapoula, Zoï (Frontiers in Neurology, 2016)
Clinical studies in nonspecific chronic arthralgia and back pain seem to indicate an association between vertical heterophoria (VH – latent vertical retinal misalignment) and asymmetrical head rotation. Such clinical observations suggest a link between VH and head rotation, but this was never tested. The purpose of this study was to simulate a VH in healthy subjects, and examine its influence on the amplitude of active head rotation during 3D motion capture in upright stance. Subjects were asked to rotate their head three times from the straight ahead position and then to the right, back to straight ahead, to the left, and back to the straight ahead again. Three randomized conditions were run: normal viewing, with a one-diopter prism base down on the dominant eye, or the non-dominant eye. The most important finding is that the experimental VH whichever the eye with the prism induces a significant decrease in the mean angle of head rotation compared to the normal viewing condition. This decrease was significant for rotation to the left. We suggest that the prism-induced VH modifies the reference posture and thereby affects head rotation; further studies are needed to confirm this effect, and to extend to other types of dynamic activities.